Characterization of Palm Kernel Oil as Raw Material for Transparent Soap - Febrina, Wetri; Noviani, Dewi (ADPEBI, 2022)
Soap is a product of a saponification reaction involving oil/fat and alkali which functions to decrease the surface tension so as to help clean dirt. Palm kernel oil with the main fatty acid content in the form of lauric has good properties for making solid type soap, namely hardening, cleaning and producing abundant foam. The purpose of this study was to analyze the characteristics of palm kernel oil as a raw material for transparent solid soap and to test the quality of the resulting soap. In this study, transparent soap was made with glycerin, sucrose and 96% ethanol as a transparent agent that met the requirements for quality testing and organoleptic testing. The method of making soap using the semi-boiled method is mixing palm kernel oil with stearic acid which has been melted at a temperature of 60oC, then added 30% NaOH carried out with stirring at a temperature of 70-800 C. Keywords : transparent soap, crude palm kernel oil, saponification